Superficial Macula Capillary Complexity Changes Are Associated With Disability in Neuromyelitis Optica Spectrum Disorders - Wei, Ruili; Xie, Jianyang; Wu, Huihui; He, Fangping; Meng, Fangxia; Liu, Jiang; Liang, Hui; Zhao, Yitian (Frontiers in Neurology, 2021)
Purpose: We examined the microvascular changes of the macula in neuromyelitis optica spectrum disorders (NMOSD) patients and its association with their disability and other clinical variables. Methods: Thirty-four NMOSD (13 patients without optic neuritis, NMOSD-NON, and 21 patients with a history of optic neuritis, NMOSD-ON) and 44 healthy controls (HCs). Optical coherence tomographic angiography (OCTA) was used to image the superficial (SCP), deep (DCP), and whole capillary plexus (WCP) in a 2.5-mm diameter concentric circle (excluding the foveal avascular zone, FAZ). An algorithm (Dbox) was used to quantify the complexity of the three capillary layers by fractal analysis. We also evaluated the expanded disability scale status (EDSS) Results: Dbox values were significantly reduced in SCP (P < 0.001), DCP (P < 0.001) and WCP (P = 0.003) of NMOSD when compared to HCs. Dbox values were significantly reduced in eyes with optic neuritis when compared with healthy controls (P < 0.001) and eyes without optic neuritis (P = 0.004) in the SCP. In the DCP, eyes with optic neuritis showed significantly reduced Dbox values when compared to eyes without optic neuritis (P = 0.016) and healthy controls (P < 0.001); eyes without optic neuritis showed significantly reduced Dbox values (P = 0.007) in the DCP when compared to healthy controls. A significant negative correlation (Rho = -0.475, P = 0.005) was shown between the superficial macula Dbox values and the EDSS in NMOSD patients. Additionally, a negative correlation (Rho = -0.715, P = 0.006) was seen in the superficial Dbox values in eyes without optic neuritis and EDSS. Conclusions: Microvascular damage in the superficial plexus is associated with disability in NMOSD. Macula microvascular alterations arise independently of the occurrence of ON in NMOSD.